Preparation method of low-loss high-direct-current-superposition iron-silicon / iron-nickel composite magnetic powder core
Through the preparation method of the ferrosilicon/ferro-nickel composite magnetic powder core, combined with preheating, passivation and annealing treatment, the problem of high power loss of the ferrosilicon magnetic powder core at high frequency and high power is solved, and the effect of low loss and high DC superposition is achieved.
Patent Information
- Application Number
- CN202510869200.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-08-29
AI Technical Summary
The existing ferrosilicon magnetic powder cores have high power losses in high-frequency and high-power applications, making it difficult to meet the needs of small electronic components.
By mixing the ferrosilicon magnetic powder with the ferrosilicon magnetic powder with the ferrosilicon magnetic powder and performing preheating treatment, passivation treatment, physical coating and annealing treatment, a low loss and high DC superposition of ferrosilicon/ferrosilicon composite magnetic powder core is prepared.
It effectively reduces the power loss of the magnetic powder core, improves the DC superposition characteristics and resistivity, and meets the performance requirements of electronic components for soft magnetic materials.
Smart Images

Figure CN120565276A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a method for preparing a low-loss, high-DC superimposed iron-silicon / iron-nickel composite magnetic powder core. Background Art
[0002] Metal powder cores are widely used in the electrical industry due to their high saturation flux density and effective permeability. As electronic components in industrial products such as home appliances, automobiles, and mobile phones continue to trend toward miniaturization and intelligence, reducing the power loss of powder cores in high-frequency, high-power applications is essential to adapting to this development.
[0003] A search revealed a Chinese patent document with publication number CN118969429A, which discloses a method for preparing an iron-silicon magnetic powder core. The method involves grading iron-silicon magnetic powders and then combining them. The powders are then subjected to a first heat treatment in a protective atmosphere, followed by an oxidation treatment to form an oxide film. This is then subjected to a reduction treatment to partially or completely reduce the oxide film to ferroferric oxide. The powders are then pressed and formed, followed by a second heat treatment in a protective atmosphere. The resulting iron-silicon magnetic powder core has a power loss of a minimum of 564 mW·cm at 50 kHz and 100 mT. -3 The magnetic powder core prepared by the above method has significantly higher power loss and is not suitable for application scenarios of small electronic components.
[0004] In view of this, the inventors hope to provide a method for preparing an iron-silicon / iron-nickel composite magnetic powder core with low power loss, high DC superposition, and low price, which can effectively reduce the power loss of the iron-silicon magnetic powder core while ensuring excellent other magnetic properties. Summary of the Invention
[0005] The purpose of the present invention is to overcome the above-mentioned problems existing in the traditional technology and provide a method for preparing a low-loss, high-DC superimposed iron-silicon / iron-nickel composite magnetic powder core.
[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0007] The present invention provides a method for preparing a low-loss, high-DC superimposed iron-silicon / iron-nickel composite magnetic powder core, comprising the following steps:
[0008] S1. Preheating treatment: heat treatment of ferrosilicon magnetic powder;
[0009] S2. Powder mixing: adding iron-nickel magnetic powder to the heat-treated iron-silicon magnetic powder and mixing them evenly to obtain mixed magnetic powder;
[0010] S3, passivation treatment: mixing the mixed magnetic powder with the passivation solution, performing passivation treatment, and obtaining alloy powder;
[0011] S4. Physical coating: Take appropriate amount of magnesium aluminum silicate gel, silica sol and passivated alloy powder and mix them thoroughly, heat the mixed system and mechanically stir until the powder is dry;
[0012] S5. Pressing and molding: mechanically stirring the physically coated magnetic powder and lubricant, mixing them evenly, and pressing them into magnetic powder core blanks;
[0013] S6. Annealing treatment: Annealing treatment is performed on the pressed blank to release internal stress.
[0014] Furthermore, in step S1, the alloy composition of the ferrosilicon magnetic powder is: Fe accounts for 96.2wt% and Si accounts for 3.8wt%.
[0015] Furthermore, in step S1, the particle size of the iron silicon magnetic powder is 38 to 74 μm.
[0016] Furthermore, in step S1, the primary heat treatment is performed in an N2 or H2 atmosphere at 650-900°C for 0.5-1.5h.
[0017] Furthermore, the heat treatment heating rate is 5-10°C / min, and the cooling method is natural cooling with the furnace.
[0018] Furthermore, in step S2, the alloy composition of the iron-nickel magnetic powder is: Fe accounts for 50wt%, and Ni accounts for 50wt%.
[0019] Furthermore, the particle size of the iron-nickel magnetic powder is less than 38 μm, and the content of the iron-nickel magnetic powder is controlled to be 10-30 wt % of the iron-silicon magnetic powder.
[0020] Furthermore, in step S3, the passivation agent used in the passivation solution is a mixture of chromic acid and chromate, the chromic acid accounts for 0.02-0.8 wt% of the mass of the mixed magnetic powder, and the chromate accounts for 0.01-0.4 wt% of the mass of the mixed magnetic powder.
[0021] Furthermore, in step S6, the temperature of the annealing treatment is controlled at 650-750° C., H 2 is used as the protective atmosphere, and the annealing treatment time is controlled at 0.5-1.5 h.
[0022] The beneficial effects of the present invention are:
[0023] 1. Mixing large-particle iron-silicon alloy powder with small-particle iron-nickel alloy powder can prevent the iron-nickel particles from deforming to a large extent, while improving the DC superposition characteristics of the magnetic powder core and reducing power loss.
[0024] 2. Preheat the magnetic powder in N2 or H2 atmosphere to grow the particle grains and reduce the grain boundaries, effectively reducing the hysteresis loss of the magnetic powder core.
[0025] 3. A passivation film forms on the surface of the passivated alloy powder, which increases the resistivity of the magnetic powder core. The use of magnesium aluminum silicate to coat the magnetic powder can further enhance the coating effect. The coated magnetic powder has a good dispersion effect, and the excess coating agent can act as a filler to ensure the integrity of the coating layer during molding.
[0026] 4. Anneal the magnetic powder core blank in H2 atmosphere to prevent further oxidation of the blank and reduce the power loss of the magnetic powder core.
[0027] 5. The low-loss iron silicon magnetic powder core prepared by the present invention has excellent soft magnetic properties and low power loss, which meets the requirements of electronic components for the performance of soft magnetic materials.
[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 This is the cross-sectional micromorphology of the magnetic powder core prepared from magnetic powder after hydrogen preheating treatment. DETAILED DESCRIPTION
[0031] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0032] The alloy composition of the iron silicon magnetic powder is as follows: Fe accounts for 96.2wt%, Si accounts for 3.8wt%, and is recorded as FeSi3.8.
[0033] The alloy composition of the iron-nickel magnetic powder is as follows: Fe accounts for 50wt%, Ni accounts for 50wt%, and is recorded as FeNi.
[0034] Example 1
[0035] Aerosolized FeSi3.8 magnetic powder with a particle size of 38-74 μm was preheated at 700°C in a H2 atmosphere for 1 hour and then mixed with aerosolized FeNi magnetic powder with a particle size of less than 38 μm, with the aerosolized FeNi powder accounting for 20 wt% by weight. The mixed magnetic powder was passivated by adding 0.03 wt% chromic acid and 0.2 wt% potassium dichromate, based on the mass of the mixed magnetic powder. The passivated magnetic powder was coated and bonded with a mixture of 1.0 wt% magnesium aluminum silicate gel and 0.4 wt% silica sol as a coating and binder, and heated and stirred until dry. The physically coated magnetic powder was then mixed with 0.3 wt% zinc stearate and pressed into a blank at 2000 MPa. Finally, the blank was annealed at 700°C in a H2 atmosphere to prepare a magnetic powder core sample.
[0036] Example 2
[0037] Aerosolized FeSi3.8 magnetic powder with a particle size of 38-74 μm was preheated at 800°C in a H2 atmosphere for 1 hour and then mixed with aerosolized FeNi magnetic powder with a particle size less than 38 μm, with the aerosolized FeNi powder accounting for 20 wt% by weight. The mixed magnetic powder was passivated by adding 0.06 wt% chromic acid and 0.2 wt% potassium dichromate, based on the mass of the mixed magnetic powder. The passivated magnetic powder was then coated and bonded with a mixture of 1.0 wt% magnesium aluminum silicate gel and 0.2 wt% silica sol as a coating and binder. The physically coated alloy powder was then mixed with 0.3 wt% zinc stearate and pressed into a blank at 2000 MPa. Finally, the blank was annealed at 700°C in a H2 atmosphere to prepare a magnetic powder core sample.
[0038] Example 3
[0039] Aerosolized FeSi3.8 magnetic powder with a particle size of 38-74 μm was preheated at 850°C in a nitrogen atmosphere for 1 hour and then mixed with aerosolized FeNi magnetic powder with a particle size less than 38 μm, with the aerosolized FeNi powder accounting for 30% by weight. The mixed magnetic powder was passivated by adding 0.1% chromic acid and 0.2% potassium dichromate, based on the mass of the mixed magnetic powder. The passivated magnetic powder was then coated and bonded with a mixture of 0.8% magnesium aluminum silicate gel and 0.4% silica sol as a coating and binder. The physically coated magnetic powder was then mixed with 0.3% zinc stearate and pressed into a blank at a pressure of 2000 MPa. Finally, the blank was annealed at 750°C in a hydrogen atmosphere to prepare a magnetic powder core sample.
[0040] Example 4
[0041] Aerosolized FeSi3.8 magnetic powder with a particle size of 38-74 μm was preheated at 850°C in a nitrogen atmosphere for 1 hour and then mixed with aerosolized FeNi magnetic powder with a particle size less than 38 μm, with the aerosolized FeNi powder accounting for 10 wt%. The mixed magnetic powder was passivated by adding 0.3 wt% chromic acid and 0.4 wt% potassium dichromate, based on the mass of the mixed magnetic powder. The passivated magnetic powder was then coated and bonded with a mixture of 0.6 wt% magnesium aluminum silicate gel and 0.3 wt% silica sol as a coating and binder. The physically coated magnetic powder was then mixed with 0.3 wt% zinc stearate and pressed into a blank at 2000 MPa. Finally, the blank was annealed at 750°C in a hydrogen atmosphere to prepare a magnetic powder core sample.
[0042] Comparative Example 1
[0043] Aerosolized FeSi3.8 magnetic powder with a particle size of 38 to 74 μm was uniformly mixed with aerosolized FeNi magnetic powder with a particle size of less than 38 μm, with the aerosolized FeNi powder accounting for 20 wt%. Based on the mass of the mixed magnetic powder, 0.03 wt% chromic acid and 0.2 wt% potassium dichromate were added to the mixed magnetic powder to passivate the magnetic powder. The passivated magnetic powder was coated and bonded with a mixture of 1.0 wt% magnesium aluminum silicate gel and 0.4 wt% silica sol as a coating and binder, and heated and stirred until dry. The physically coated magnetic powder was then mixed with 0.3 wt% zinc stearate and pressed into a blank at a pressure of 2000 MPa. Finally, the blank was annealed at 700°C in a H2 protective atmosphere to prepare a magnetic powder core sample.
[0044] Comparative Example 2
[0045] Aerosolized FeSi3.8 magnetic powder with a particle size of 38-74 μm was preheated at 800°C in an H2 atmosphere for 1 hour and then mixed with aerosolized FeNi magnetic powder with a particle size less than 38 μm, with the aerosolized FeNi powder accounting for 20 wt% by weight. The mixed magnetic powder was then passivated by adding 0.06 wt% chromic acid and 0.2 wt% potassium dichromate, based on the mass of the mixed magnetic powder. The passivated magnetic powder was then coated and bonded with a mixture of 1.0 wt% magnesium aluminum silicate gel and 0.2 wt% silica sol as a coating and binder. The physically coated alloy powder was then mixed with 0.3 wt% zinc stearate and pressed into a blank at 2000 MPa. Finally, the blank was annealed at 700°C in an N2 atmosphere to prepare a magnetic powder core sample.
[0046] Comparative Example 3
[0047] Aerosolized FeSi3.8 magnetic powder with a particle size of 38-74 μm was preheated at 850°C in a nitrogen atmosphere for 1 hour. Based on the mass of the FeSi3.8 magnetic powder, 0.06 wt% chromic acid and 0.2 wt% potassium dichromate were added to the magnetic powder to passivate it. The passivated magnetic powder was then coated and bonded with a mixture of 1.0 wt% magnesium aluminum silicate gel and 0.2 wt% silica sol as a coating and binder. After physical coating, 0.3 wt% zinc stearate was added and mixed uniformly. The resulting blanks were then pressed under a pressure of 2000 MPa and annealed at 750°C in a hydrogen atmosphere to prepare magnetic powder core samples.
[0048] The prepared iron silicon magnetic powder core is wound with 20 turns of enameled copper wire with a diameter of Φ = 0.8 mm to measure its inductance L and DC superposition performance %μ e , wound 20 turns of double-stranded wire to measure its power loss. The soft magnetic properties of Examples 1 to 4 and Comparative Examples 1 to 3 were measured, as shown in Table 1:
[0049] Table 1
[0050]
[0051] From Table 1, we can get:
[0052] The low-loss iron-silicon-iron-nickel composite magnetic powder cores prepared by the method of the present invention have effective permeabilities slightly higher than those of comparative examples 1 to 2 in Examples 1 to 4, and DC superposition characteristics at 100 Oe are higher than those of comparative examples 1 to 3. The power loss of Examples 1 to 4 is significantly lower than that of comparative examples 1 to 3, with the power loss of the magnetic powder core of Example 3 being as low as 378.8 mW / cm at 50 kHz and 100 mT. 3 .
[0053] Compared with Example 1, the preheating temperature of Example 2 is increased from 700°C to 800°C, and its power loss is significantly reduced. Higher temperature is conducive to the growth of grain size. Compared with Example 3, the iron and nickel content of Example 4 is increased, and the power loss of the magnetic powder core is reduced to 378.8mW / cm 3 (50kHz, 100mT), the DC superposition characteristic is improved to 86.37%.
[0054] The iron silicon magnetic powder used in Comparative Example 1 was not preheated. Compared with Example 1, it was shown that the preheating process was related to the soft magnetic properties of the magnetic powder core, and the power loss of the magnetic powder core prepared by the preheated magnetic powder was reduced.
[0055] Comparison of the test results of Comparative Example 2 with those of Example 1 shows that the magnetic properties of the magnetic powder core decreased after annealing under N2 protection. The DC superposition characteristic was 81.31% at 100Oe, and the power loss increased to 501.7mW / cm at 50kHz and 100mT.3 ; Its power loss is significantly worsened.
[0056] Comparative Example 3 is compared with Example 3. Iron silicon is directly used as the raw material, and its power loss is significantly higher and the DC superposition characteristic is poor.
[0057] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a low-loss, high-DC superimposed iron-silicon / iron-nickel composite magnetic powder core, characterized in that: The steps include: S1. Preheating treatment: heat treatment of ferrosilicon magnetic powder; S2. Powder mixing: adding iron-nickel magnetic powder to the heat-treated iron-silicon magnetic powder and mixing them evenly to obtain mixed magnetic powder; S3, passivation treatment: mixing the mixed magnetic powder with the passivation solution, performing passivation treatment, and obtaining alloy powder; S4. Physical coating: Take appropriate amount of magnesium aluminum silicate gel, silica sol and passivated alloy powder and mix them thoroughly, heat the mixed system and mechanically stir until the powder is dry; S5. Pressing and molding: mechanically stirring the physically coated magnetic powder and lubricant, mixing them evenly, and pressing them into magnetic powder core blanks; S6. Annealing treatment: Annealing treatment is performed on the pressed blank to release internal stress.
2. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 1, characterized in that: In step S1 , the alloy composition of the iron-silicon magnetic powder is as follows: Fe accounts for 96.2 wt % and Si accounts for 3.8 wt %.
3. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 1, characterized in that: In step S1, the particle size of the iron silicon magnetic powder is 38-74 μm.
4. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 1, characterized in that: In step S1, the primary heat treatment is performed in an N2 or H2 atmosphere at 650-900°C for 0.5-1.5h.
5. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 4, characterized in that: The heating rate of the heat treatment is 5-10°C / min, and the cooling method is natural cooling with the furnace.
6. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 1, characterized in that: In step S2, the alloy composition of the iron-nickel magnetic powder is: Fe accounts for 50 wt% and Ni accounts for 50 wt%.
7. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 1, characterized in that: The particle size of the iron-nickel magnetic powder is less than 38 μm, and the content of the iron-nickel magnetic powder is controlled to be 10-30 wt % of the iron-silicon magnetic powder.
8. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 1, characterized in that: In step S3, the passivation agent used in the passivation solution is a mixture of chromic acid and chromate, wherein the chromic acid accounts for 0.02-0.8 wt% of the mass of the mixed magnetic powder, and the chromate accounts for 0.01-0.4 wt% of the mass of the mixed magnetic powder.
9. The method for preparing a low-loss, high-DC superimposed Fe-Si / Fe-Ni composite magnetic powder core according to claim 1, characterized in that: In step S6, the temperature of the annealing treatment is controlled at 650-750° C., H 2 is used as the protective atmosphere, and the annealing treatment time is controlled at 0.5-1.5 h.
Citation Information
Patent Citations
Iron-silicon magnetic powder core and preparation method and application thereof
CN118969429A
Cited By
Iron-silicon waste material recycling method and iron-silicon magnetic powder core
CN121416254A
